Cultural Repercussions: Extending Our Knowledge about How Values of Trust and Confidence Influence Tax Structures within Europe - Hanna Lierse; Rune Ellemose Gulev (International School for Social and Business Studies, 2012)
Within a unified Europe that is heading towards ever more harmonization,it is interesting to examine why there exists such diversity in tax regimesamong its countries. Is it possible that some of the decisions pertaining totaxation are based on latent cultural aspects? This study, set in a purelyEuropean context, seeks to analyze tax variations within Europe through thelens of cultural variations. Specifically, how trust, confidence and equalitymatter with regard to tax revenues and tax progressivity. Within this regard,we achieved strong results linking trust and confidence to higher tax revenuesand higher tax progressivity. That is, where trust among societal membersis low and confidence in public institutions is low, regimes opt for low taxrevenues and lenient tax rates. It is argued that where mistrust is high, theissue of income distribution between societal members is likely to stay withinthe private or individual sphere. Conversely, countries with high trust amongsocietal members exhibit higher levels of income distribution by delegatingmore responsibility to public institutions, reflected in higher tax revenues andmore progressive tax structures.